2006
DOI: 10.1088/0960-1317/16/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication and characterization of metal embedded thin film thermocouples with various film thicknesses and junction sizes

Abstract: Micro thin film thermocouples (TFTCs) can provide measurements with high spatial and temporal resolution. If these micro sensors can be embedded in metals, tremendous benefits can be achieved for real industrial applications. In this study, a novel batch microfabrication technique, based on the thin film transfer technique and wafer-scale embedding process, was developed to fabricate and embed thin film sensors into an electroplated nickel structure. To investigate the performance of metal embedded TFTCs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…In a calibration experiment with these two types of probes, we found that the 100 nm probe produced a temperature-thermoelectricity curve that showed an almost perfect match with the standard curve produced by a regular macro-sized TC, while the readings from the 50 nm probe showed deviations from the standard curve ( Figure 1B and 1C and Supplementary information, Figure S2). This result is consistent with earlier reports that when the thickness of the Pt film decreases beyond the 100 nm range, it will affect the resulting thermoelectric power compared to the macrosized TC at the same temperature [6,7]. Thus, we have chosen the 100 nm probe in further experiments.…”
supporting
confidence: 89%
“…In a calibration experiment with these two types of probes, we found that the 100 nm probe produced a temperature-thermoelectricity curve that showed an almost perfect match with the standard curve produced by a regular macro-sized TC, while the readings from the 50 nm probe showed deviations from the standard curve ( Figure 1B and 1C and Supplementary information, Figure S2). This result is consistent with earlier reports that when the thickness of the Pt film decreases beyond the 100 nm range, it will affect the resulting thermoelectric power compared to the macrosized TC at the same temperature [6,7]. Thus, we have chosen the 100 nm probe in further experiments.…”
supporting
confidence: 89%
“…Recently, thermomechanical phenomena were studied by the use of embedded thin-film sensors for various manufacturing processes [18][19][20][21][22][23][24]. Two types of thin-film microsensors, K-type TFTC, and K-type thermocouple based TETP, were designed and fabricated for in-situ temperature measurement of ultrasonic welding process to better understand the process [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Film thickness is a critical parameter that influences the sensitivity of TFT [21]- [23]. However, the sensitivity of K-type thin-film thermocouples is independent of the film thickness when the it is greater than140nm [24]. 16 cycles of sputter deposition with sputter current of 150mA and cycle time of 120S could yield films with thicknesses sufficiently greater than this threshold.…”
Section: B Sensor Fabricationmentioning
confidence: 99%